Analisis Pengendalian Persediaan Bahan Baku Dalam Upaya Menekan Biaya Produksi Pada Home Industry Alfaro Alumunium Mulyosari - Pratama, Andika; Riyanto, Kuncoro Budi (Universitas Muhammadiyah Metro, 2022)
Home industry Alfaro Aluminum as one of the companies engaged in the aluminum processing industry in Mulyosari Metro Barat. The problem that often occurs in the Alfaro Aluminum home industry is to carry out proper inventory control due to increases and decreases in orders and in certain months. Storage of raw materials that are not good will cause damage, such as glass that breaks easily when hit by an attack, spigot that bends easily, and wheels that get jammed easily. The purpose of this study was to determine the optimal number of orders for raw materials at the Alfaro Aluminum home industry using the EOQ method, to determine the optimal purchase frequency at the Alfaro Aluminum home industry using the EOQ method, to determine the amount of safety stock that must be available to maintain the production process and to find out the difference in the amount of inventory that the company can save when using the EOQ method in the Alfaro Aluminum home industry. This type of research is a qualitative research that is comparing the data collected with the basis as a reference material in several problem solving solutions. The results of this study are the optimal number of orders for raw materials for the company is 191 pcs for each order. The optimal purchase frequency when using the EOQ method is 12 times. The optimal safety stock when using the EOQ method is 12.33 pcs. The difference in the amount of inventory that can be saved if using the EOQ method is Rp. 1,440,112.63 for each year. Keywords: Home Industry, EOQ Method, Raw Material Inventory Control